2011
DOI: 10.1021/je101014q
|View full text |Cite
|
Sign up to set email alerts
|

Low-Viscosity Triethylbutylammonium Acetate as a Task-Specific Ionic Liquid for Reversible CO2 Absorption

Abstract: Capturing and storing carbon dioxide (CO2) is now of concern. This work presents a task-specific ionic liquid (TSIL), triethylbutylammonium acetate ([N2224][CH3COO]), for the purpose of trapping CO2 instead of the commonly used organic amine solutions. Since [N2224][CH3COO] has a hydrophilic nature, the CO2 dissolution behavior into [N2224][CH3COO]−nH2O complexes has been investigated in detail, including the absorption rate, absorption capacity, and the ability of repeating absorption. The solubilities of CO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 39 publications
6
66
0
1
Order By: Relevance
“…43 The authors concluded that "the overall tendency is that adding a certain amount of water into the pure ionic liquids will slightly decrease the absorption capacity of CO 2 , but the lower viscosity of the mixture is favourable as it can promote gas diffusion in the solvent and reduce operational constrains on the use of ionic liquids fluids". 62,64 Of the multitude of papers on carbon dioxide solubility in ionic liquids, those that mention water content, with very few exceptions, state that the ionic liquids must be as dry as possible. 62,64 Of the multitude of papers on carbon dioxide solubility in ionic liquids, those that mention water content, with very few exceptions, state that the ionic liquids must be as dry as possible.…”
Section: Anhydrous Carboxylate Ionic Liquidsmentioning
confidence: 99%
“…43 The authors concluded that "the overall tendency is that adding a certain amount of water into the pure ionic liquids will slightly decrease the absorption capacity of CO 2 , but the lower viscosity of the mixture is favourable as it can promote gas diffusion in the solvent and reduce operational constrains on the use of ionic liquids fluids". 62,64 Of the multitude of papers on carbon dioxide solubility in ionic liquids, those that mention water content, with very few exceptions, state that the ionic liquids must be as dry as possible. 62,64 Of the multitude of papers on carbon dioxide solubility in ionic liquids, those that mention water content, with very few exceptions, state that the ionic liquids must be as dry as possible.…”
Section: Anhydrous Carboxylate Ionic Liquidsmentioning
confidence: 99%
“…Ionic liquids (ILs) are extensively reported as a kind of new and ''promising'' absorbent for CO 2 in the past two decades due to their unique properties, such as high thermal stability, extremely low volatility, diversity, and tuneable properties [9][10][11]. However, ionic liquids still have several shortcomings including high price, complicated technology for production and purification, uncertain toxicity and poor biodegradability [12].…”
Section: Introductionmentioning
confidence: 99%
“…es batu pada kotak styrofoam untuk menjaga suhu media tetap stabil pada suhu rendah. Peningkatan suhu menyebabkan peningkatan viskositas dan juga menyebabkan penurunan kelarutan gas dalam air, misalnya gas O 2 , CO 2 , N 2 , dan CH 4 (Goodrich et al, 2011;Wang et al, 2011;Nishizaki & Carrington, 2014 …”
Section: Analisis Dataunclassified